Longterm clinical outcomes of omalizumab therapy in severe allergic asthma: Study of efficacy and safety. (March 2017) - Mansur, Adel H.; Srivastava, Sapna; Mitchell, Verity; Sullivan, Julie; Kasujee, Ismail
Abstract: Omalizumab has been shown to be an effective add-on therapy for patients with uncontrolled severe persistent allergic asthma. There has been a steady accumulation of evidence on the long-term effectiveness of omalizumab; however, data on real-life outcomes beyond one year of treatment is limited. In this study, we report on long-term outcomes of omalizumab treatment. We collected data from our severe asthma registry on hospitalisations, exacerbations, corticosteroid sparing, asthma control, lung function, biomarkers and side effects, to determine if the benefit was sustained and treatment was safe on the long term. Forty-five patients [mean age 44.9 years (range 19–69), females 37/45 (82%), mean duration of omalizumab treatment = 60.7 ± 30.9 months (range 23–121) were included in the analysis. We observed a reduction in the annual acute asthma related hospital admissions for the total population from 207 at baseline to 40 on treatment (80.7% reduction), whilst the per patient annual hospitalisations were reduced from a mean of 4.8 to 0.89 post-omalizumab treatment (p < 0.00001). There was a 76.7% reduction in daily mean maintenance OCS dose (prednisolone equivalent) from 25.8 mg (n = 43) to 6.0 mg (p < 0.0001), associated with clinically significant improvement in asthma control questionnaire (ACQ) from mean score of 4.1 (range 3.7–4.7) to 2.27 (range 0.5–4.1) p < 0.0001. The mean % predicted FEV1 has improved from 59.2% at baseline to 75.7% on treatment (p = 0.001). There was a statistically non-significant reduction in median peripheral blood eosinophils (PBE) from 300 cells/μl (range 40–1050) at baseline to 175 cells/μl (range 0–1500) post-treatment (p = 0.068), and statistically significant reduction of median fraction exhaled nitric oxide (FeNO) level from 37 parts per billion (range 12–178) to 24 ppb (range 7–50) (p = 0.0067). The work/school missed days were reduced in 17/19 patients who were at employment or school. The overall safety profile of the treatment seemed acceptable and was consistent with published experience. In conclusion, results from this real-life study demonstrate that improved outcomes in patients with severe allergic asthma are sustained with longer-term omalizumab therapy.